Um escândalo (não tão) íntimo: estratégias de relações públicas na construção do storytelling midiático e imagem da cantora Luísa Sonza - (:unkn) unknown (Universidade Federal do Pampa, 2024)
The main goal of this monography was to understand how the promotional strategies for the album Escândalo Íntimo relate to the construction of the image and media storytelling of singer Luísa Sonza in order to establish a relationship with her audiences. To reach this goal, the following specific objectives were listed: to systematize the promotional strategies for the album Escândalo Íntimo by collecting content from news sites and social networks of the artist; to contextualize the biography of the artist from the perspective of the media storytelling constructed by her in relation to the album Escândalo Íntimo; and to identify and analyze the perspectives of Luísa Sonza's fans based on the strategies addressed. Methodologically, the research is characterized as exploratory and qualitative, using documentary data collection procedures (media news and song lyrics), as well as questionnaires with fans through Google Forms. Luísa Sonza's biographical trajectory was briefly contextualized, bringing it closer to the theoretical concepts of image construction, reputation, media storytelling and fan culture. Then, an analysis was made for four songs from the album Escândalo Íntimo (Campo de Morango, Chico, Penhasco2 and Principalmente Me Sinto Arrasada) to understand the narrative told by the media about Luísa Sonza's life and how she appropriated this to create her own storytelling based on the songs. Finally, Luísa's fans were asked to answer to questionnaires to understand their interpretations of the strategies she used to promote the album to establish relationships with her audiences.
Keywords: Imagem (Psicologia); Mídia social; Terapia narrativa; Fãs (Pessoas); Artistas famosos; Marketing; Storytelling; Image (Psychology); Social Media; CNPQ::CIENCIAS SOCIAIS APLICADAS